The metamorphic rocks of the Nunatak Viedma in the Southern Patagonian Andes: Provenance sources and implications for the early Mesozoic Patagonia-Antarctic Peninsula connection - Suárez, Rodrigo Javier (2019)
Fil: Suárez, Rodrigo Javier. Instituto de Estudios Andinos IDEAN (Universidad de Buenos Aires - CONICET), Buenos Aires, Argentina